Forecasting the recovery of COVID-19 patients in East Java using the Fuzzy time series Cheng method - Tony Yulianto; Faisol Faisol; Fatimatus Zahroh; Sri Suryanti; Mohamad Tafrikan (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
Coronavirus 2019 (COVID-19) has significantly impacted Indonesia. Social restrictions in Indonesia's major cities and rural areas have been put in place as the coronavirus spreads. The Indonesian government is more vigilant with the spread of COVID-19, namely by issuing a lockdown policy to PSBB (Large-Scale Social Restrictions). Almost all Indonesian people have complied with the guidelines set by the government, namely carrying out all activities in a WFH manner to minimize the chain of distribution of COVID-19 in Indonesia. The author of this work forecasts the recovery rate of Covid-19 patients in the East Java region using the Cheng Fuzzy Time Series approach. After checking the simulation with real in the field, it can be seen that using 51 data starting from February 4 2021 to March 26 2021 gives results MAPE = 0.4602%, which means the forecasting is very accurate.©2021 JNSMR UIN Walisongo. All rights reserved.